PATTERNS OF STRUCTURAL ORGANIZATION OF THE BRONCHOPULMONARY SYSTEM IN CLINICALLY HEALTHY WHITE OUTBRED RATS - Zharlykassynova , G.; Boltaeva , Z. (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
The study evaluates the structural and morphometric features of the bronchopulmonary system in clinically healthy white outbred rats to establish reference parameters. Thirty rats (6, 9, and 12 months) were examined using histological and morphometric methods. An age-dependent increase in bronchial epithelium height, basement membrane thickness, and interalveolar septa was identified, most pronounced in 12-month-old animals. The findings reflect physiological tissue maturation without pathological changes. The obtained data can serve as baseline values for experimental studies of respiratory pathology.